Analisis Mutu Fisik dan Kimia Masker Wajah Tradisional Sumbawa (Seme Babak) dari Kulit Batang Pohon Mangga Golek (Mangifera indica Linn) - Septianingsih, Rika Dwi; Tanggasari, Devi (Department of Pharmacy, Bumigora University, 2023)
The people in Sumbawa Regency, especially in Pungkit village, have been using traditional face mask products, namely the Seme Babak mask, which protects facial skin from the sun when doing activities all day outside the room. The traditional Seme Babak mask is made from the main ingredients, namely mango tree trunks and rice supporting ingredients, white glutinous rice and jackfruit seeds. The purpose of this study was to deterne the physical quality (spreadability, absorption, adhesion, particle size, homogeneity, moisture content) and to determine the chemical quality of the Seme Babak Typical Sumbawa masks with antioxidants and pH. This type of research is observational research and laboratory experiments. Based on the results of laboratory tests, the physical test results obtained an average particle size of 60 mesh or 0.25 mm, absorption power of 8 ml, adhesion of 6.43 seconds, spreadability of 5.1 cm, homogeneity, moisture content of 11% and chemical test results, the average value of the antioxidant test the IC50 value of the Seme Babak powder mask preparation is classified as a strong antioxidant at an IC50 value of more than 50 and less than 100, namely 68.2212 ppm and the pH level meets the requirements, namely the pH level because the pH value is in the range of 4.5-8.0.